Pengaruh Kepemimpinan Transformasional dan Kecerdasan Emosional Terhadap Loyalitas Karyawan PT. Pegadaian Tente - Dewi Ainun Fajriani; Muhammad Yusuf; Mawar Hidayanti (Indo Publishing, 2026)
This study aims to determine and analyze the influence of transformational leadership and emotional intelligence on employee loyalty at PT. Pegadaian Tente. This research employed a quantitative approach with an associative research design. The population consisted of 37 employees of PT. Pegadaian Tente, all of whom were selected as the research sample using the saturated sampling technique. Data were collected through observation, questionnaires using a Likert scale, and literature review. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test, and F-test with the assistance of SPSS version 26. The results indicate that transformational leadership has a significant effect on employee loyalty, with a t-value of 2.396 and a significance value of 0.022 (< 0.05). Emotional intelligence also has a significant effect on employee loyalty, with a t-value of 5.481 and a significance value of 0.000 (< 0.05). Simultaneously, transformational leadership and emotional intelligence have a significant effect on employee loyalty, with an F-value of 144.181 and a significance value of 0.000 (< 0.05). The coefficient of determination (R²) is 0.895, indicating that 89.5% of the variation in employee loyalty can be explained by transformational leadership and emotional intelligence, while the remaining 10.5% is influenced by other factors not examined in this study. Based on the findings, it can be concluded that transformational leadership and emotional intelligence have a positive and significant influence, both partially and simultaneously, on employee loyalty at PT. Pegadaian Tente. Therefore, the company is expected to continuously improve transformational leadership practices and enhance employees' emotional intelligence to strengthen their loyalty toward the organization.